Camel milk is a neglected source of brucellosis among rural Arab communities - Peter Holloway; Matthew Gibson; Tanja Holloway; Iain Pickett; Brittany Crook; Jacqueline M. Cardwell; Stephen Nash; Imadidden Musallam; Bilal Al-Omari; Ahmad Al-Majali; Wail Hayajneh; Ehab Abu-Basha; et al. (Nature Communications)
Abstract The World Health Organization describes brucellosis as one of the world’s leading zoonotic diseases, with the Middle East a global hotspot. Brucella melitensis is endemic among livestock populations in the region, with zoonotic transmission occurring via consumption of raw milk, amongst other routes. Control is largely via vaccination of small ruminant and cattle populations. Due to sociocultural and religious influences camel milk (camelus dromedarius) is widely consumed raw, while milk from other livestock species is largely boiled. To investigate the potential public health impact of Brucella in camels we conduct a cross-sectional study in southern Jordan including 227 herds and 202 livestock-owning households. Here we show daily consumption of raw camel milk is associated with Brucella seropositive status among the study population, ORadj 2.19 (95%CI 1.23–3.94) on multivariable analysis, highlighting the need for socioculturally appropriate control measures; targeted interventions among the camel reservoir being crucial for effective control.